Export of cyst wall material and Golgi organelle neogenesis in Giardia lamblia depend on endoplasmic reticulum exit sites. (2nd December 2012) - Faso, Carmen; Konrad, Christian; Schraner, Elisabeth M.; Hehl, Adrian B.
Summary Giardia lamblia parasitism accounts for the majority of cases of parasitic diarrheal disease, making this flagellated eukaryote the most successful intestinal parasite worldwide. This organism has undergone secondary reduction/elimination of entire organelle systems such as mitochondria and Golgi. However, trophozoite to cyst differentiation (encystation) requires neogenesis of Golgi‐like secretory organelles named encystation‐specific vesicles (ESVs), which traffic, modify and partition cyst wall proteins produced exclusively during encystation. In this work we ask whether neogenesis of Golgi‐related ESVs during G. lamblia differentiation, similarly to Golgi biogenesis in more complex eukaryotes, requires the maintenance of distinct COPII‐associated endoplasmic reticulum (ER) subdomains in the form of ER exit sites (ERES) and whether ERES are also present in non‐differentiating trophozoites. To address this question, we identified conserved COPII components in G. lamblia cells and determined their localization, quantity and dynamics at distinct ERES domains in vegetative and differentiating trophozoites. Analogous to ERES and Golgi biogenesis, these domains were closely associated to early stages ofnewly generated ESV. Ectopic expression of non‐functional Sar1 GTPase variants caused ERES collapse and, consequently, ESV ablation, leading to impaired parasite differentiation. Thus, our data show how ERES domains remain conserved in G. lamblia despite elimination of steady‐state Golgi. Furthermore, the fundamental eukaryotic principle of ERES to Golgi/Golgi‐like compartment correspondence holds true in differentiating Giardia presenting streamlined machinery for secretory organelle biogenesis and protein trafficking. However, in the Golgi‐less trophozoites ERES exist as stable ER subdomains, likely as the sole sorting centres for secretory traffic.